The Influence of Customer Satisfaction on Brand Loyalty Trough Brand Love in Samsung Smartphone Users - Suyanto, Suyanto; Geuna Tahta Archella Ardhani, Hablya (Publisher Cv. Inara, 2025)
This study investigates the impact of customer satisfaction on brand loyalty, with brand love as a mediating factor, among Samsung smartphone users at the University of Darussalam Gontor. In the competitive smartphone market, customer satisfaction alone often falls short in driving brand loyalty, highlighting the critical role of emotional connections like brand love. Using a quantitative approach, data were gathered from 171 respondents through purposive sampling and analyzed using path analysis in SPSS. Findings reveal that customer satisfaction significantly influences brand love but not brand loyalty directly, while brand love strongly impacts brand loyalty and effectively mediates the relationship. The study underscores the importance of brand love in fostering loyalty, offering theoretical insights and practical strategies for companies to strengthen emotional bonds with consumers.